All the light we cannot see a novel - Doerr, Anthony 1973- (4th Estate, 2015)
One of the most acclaimed and bestselling books of 2014. An epic novel set during WW2, from the prize-winner Anthony Doerr. When Marie Laure goes blind, aged six, her father builds her a model of their Paris neighborhood, so she can memorize it with her fingers and then navigate the real streets.